Adaptive Leadership of Principals: A Literature Review of the Challenges of Technology and Globalization in 21 st Century Education - Oktaviani, Windi Nur; Apriani, Sela; Heri, Asep; Djenjen, Djenjen; Iskandar, Sofyan (Jurnal Ilmiah Global Education, 2025)
The 21st century education faces major challenges due to technological advances and globalization that affect various aspects of learning. Principals as the main leaders in schools have a key role in managing these changes. This study aims to analyze the application of adaptive leadership by principals in facing the challenges of technology and globalization through literature studies. Based on the theory of Adaptive Leadership by Heifetz and Laurie, this study examines how principals can apply the principles of adaptive leadership to create a learning environment that is responsive to external changes and improves the quality of education a midst uncertainty. The methodology used is literature study, by analyzing various scientific articles, previous research, and relevant education policies. The results of the analysis show that principals who apply adaptive leadership are able to integrate technology into learning and adjust the curriculum to the demands of globalization. Principals also play an important role in building a culture of collaboration and innovation in schools to overcome the challenges of 21st century education. This study provides theoretical and practical contributions to the development of adaptive education policies, as well as providing recommendations for principals in leading change in the educational environment.